A Review of the Meaning of Home in Multi-Ethnic Settings - Erna Nuralia Zharani; Gehan Selim (Journal of Contemporary Urban Affairs, 2023)
This paper explores the meaning of home from multiple regions and the factors that influence the definition of home from multi-ethnic perspectives. A hypothesis derived that each ethnicity of a household practises cultural values and that reconfiguring physical spaces provides greater knowledge of their definition of home. This study employed a systematic review to gather the most relevant papers in the existing literature from the year 2000 to 2023, to address the gaps in knowledge in conceptualising the meaning of home in multi-ethnic settings. The findings respond to the hypothesis of this paper, that each household practises privacy and social boundaries in line with their belief systems and that reconfiguring physical space is part of homemaking tactics. This study outcome contributes to the development of a new conceptual framework that clarifies a comprehensive cause-effect relationship between key variables, ethnicity as the social aspect, built space as the physical aspect and practice as the personal or psychological aspect, resulting in a greater understanding of the meaning of home in multi-ethnic settings from three scenarios; the home as socio-spatial, psycho-spatial and emotive space entity.